Horticultural and Ecological Assessment of Public Gardens and Parks at Benghazi City during Last Five Decades - El Shatshat, Salem (AlQalam Journal of Medical and Applied Sciences, 2024)
Gardens and parks play significant and major role from ecological and environmental point of view. The presence of trees, plants and greenery in public gardens and resorts helps to cool the surrounding environment, reduce air pollution and improve air quality. They can also support pollinators and wild life like bees, butter flies and birds by providing a diverse range of flowering plants and habitats for urban wildlife. Despite of the ornamental plants were very limited, and the workers and specialists in this field were very rare, the municipality of Benghazi tried to provide the horticultural structures like plant nurseries, training programs and investing in employees and providing opportunities for their development. During years from 1990 to 2023, the number of gardens and parks was jumped to more than 127. Recently, more horticultural care was noticed not only in the governmental sector but also in the private one while the number of ornamental nurseries increased, private agricultural companies established, and more plants were imported and introduced to the city. Because of lack of information, we tried to analyzed and assayed the gardens and parks situation from horticultural and ecological point of view at Benghazi city from 1973 to the present using available information with focusing on the development of this sector to provide more data base for the authorities, interests and researchers. تلعب الحدائق والمتنزهات دوراً هاماً ورئيسياً من الناحية البيئية ويساعد وجود الأشجار والنباتات والمساحات الخضراء في الحدائق العامة والمنتجعات على تبريد البيئة المحيطة وتقليل تلوث الهواء وتحسين جودته. ويمكنها أيضًا دعم الملقحات والحياة البرية مثل النحل والطيور من خلال توفير مجموعة متنوعة من النباتات المزهرة والموائل للحياة البرية في المناطق الحضرية. ورغم أن نباتات الزينة كانت محدودة للغاية اضافة لندرة العاملين والمتخصصين في هذا المجال إلا أن بلدية بنغازي حاولت توفير الهياكل البستانية مثل مشاتل النباتات وبرامج التدريب والاستثمار في العاملين وإتاحة الفرص لتطويرهم. وخلال الأعوام من 1990 إلى 2023، قفز عدد الحدائق والمتنزهات إلى أكثر من 127 حديقة. وفي الآونة الأخيرة، لوحظ المزيد من الاهتمام بالبستنة ليس فقط في القطاع الحكومي ولكن أيضا في القطاع الخاص، من خلال أزدياد عدد مشاتل الزينة والشركات الزراعية الخاصة التي تم تأسيسها. وفي غياب الرقابة وجهات الاختصاص تم استيراد المزيد من النباتات الغريبة وإدخالها إلى المدينة. ونظراً لنقص المعلومات في هذا الجانب حاولنا تحليل ومعاينة وضع الحدائق والمتنزهات من الناحية البستانية والبيئية في مدينة بنغازي منذ عام 1973 حتى الوقت الحاضر باستخدام المعلومات المتاحة مع التركيز على كيفية تطوير هذا القطاع لتوفير المزيد من قاعدة البيانات لجهات الاختصاص والباحثين